Portable technology and multi-domain energy practices. (March 2020) - Robinson, Thomas Derek; Arnould, Eric
This article complements the concept of embedded security by proposing disembedded security to capture consumers' energy practices when travelling across multiple domains of energy accessibility. Consumer mobility outside the home produces misalignments between infrastructure and portable technology experienced as 'hysteresis of the battery'. Hysteresis captures how respondents are subject to 'unpleasant unpredictability' about battery-based technology and infrastructure, which spurs hermeneutic reflection about energy, location and sociality. Multi-domain energy practices therefore bring energy consumers to 'reembed' or create a sense of psychological comfort on the move. Charge levels on battery icons not only structure daily patterns of consumer life through planning efforts but become interpretively entangled in issues of duration, distance and sociality as energy demands in portable technology push consumers to avoid disruption.